O097 Developing a core outcome set for hand fractures and joint injuries in adults. (22nd July 2022) - Deshmukh, SR; Leighton, P; Montgomery, AA; Kirkham, J; Trickett, R; Jerosch-Herold, C; Rodrigues, JN; Griffin, X; Costa, ML; Karantana, A
Abstract: Introduction: A core outcome set is a baseline set of agreed upon outcomes to be used in all future clinical research on a given health topic. We aimed to develop a core outcome set for hand fractures and joint injuries in adults. Methods: We synthesised the outputs of our prior systematic review of treatment outcomes and qualitative work exploring the patient perspective to develop a longlist of outcome domains. This longlist entered a consensus prioritisation process. An international three-round Delphi survey involving patients, hand therapists and surgeons prioritised domains which were then considered in a subsequent virtual international consensus meeting involving key stakeholder groups. Using a process of discussion and prioritisation steps with pre-determined consensus criteria, the panel agreed upon a final core outcome set. Results: In the Delphi survey 41 outcome domains were rated. 144/152 participants (>94%) completed all three rounds (54 patients, 55 surgeons, 35 hand therapists). 20 domains reached consensus as very important. The final consensus meeting had 27 participants (12 patients, seven surgeons, six hand therapists, a health economist and a trial manager). After iterative prioritisation steps, a final vote selected seven outcome domains for inclusion in the core outcome set. Conclusion: Through consensus prioritisation steps we developed a final set of seven core outcome domains. These cover areas such as functional tasks, patient comfort, abstract/physiological function and patient satisfaction. They are recommended as the baseline domains to be measured in all future clinical research on hand fractures and joint injuries in adults. Take-home message: A core outcome domain set has been developed for hand fractures and joint injuries in adults, based on agreement by the key stakeholder groups. All future clinical research on these injuries should measure these domains as a baseline to improve consistency and comparability of the field of research.